School-related bullying : analysis of bullying preventive programs and analysis of power from perspective of social philosophy - Aizkalna, Viktorija (2017)
The present thesis is dedicated to a problem of school-related bullying. Bullying is a global problem that affect big number of students, and has serious short- and long-term consequences. Bullying can be manifested in various forms: it can be physical, emotional, and lately also cyber-bullying. Being a complex phenomenon, bullying can be difficult to identify, to intervene or prevent. It originates from power imbalance in a social group, and can target anyone who qualifies as “different” in any way. In order to provide analysis of bullying, in the present paper are presented definitions and analysis of the phenomenon of bullying as well global statistics of bullying across the countries in order to understand the scale of the problem and get deeper knowledge of the phenomenon of bullying to be able to prevent it more effectively. Since power is complex metaphysical concept that can not be easily defined, analysis of phenomenon is presented in the thesis. The last part of the present thesis is dedicated to analysis of two stories from former bullying victims. Both respondents who shared their experience are adults and has been conscious decision: since traumatizing experience has taken place over a decade or two ago, both respondents have had opportunity to reflect on the experience, and also can share what long-term effects they have experienced due to bullying. From the perspective of Educational Leadership, the subject of prevention of bullying is important since it affects the whole school environment. As school leaders, it is in principals’ competence and power to encourage prevention of bullying, to create positive learning environment to educate generations of emotionally and academically intelligent young people.